Molecular characterization of the ERF family in susceptible poplar infected by virulent Melampsora larici-populina. (December 2019) - Chen, Qiaoli; Wang, Zhiying; Li, Danlei; Wang, Feng; Zhang, Ruizhi; Wang, Jianan
Abstract: Melampsora larici-populina causes serious poplar foliar diseases called rust worldwide. The ethylene response factor (ERF) family, which is one of the largest groups of transcription factors (TFs) families, is considered to play a crucial role in regulating networks related to plant disease resistance. To investigate the transcript profiles of ERF genes involved in poplar rust resistance, Populus nigra  ×  P. deltoides (Pnd), which is susceptible to the E4 race of M. larici-populina, was selected for this study. Digital gene expression (DGE) libraries of mixed time points of E4-inoculated (rust+) or E4-free (rust-) Pnd leaves were examined, yielding 143 Pnd-ERF genes of which 41 Pnd-ERF genes had altered transcript levels. RT-qPCR results indicated that transcript levels of these Pnd-ERF genes were mostly reduced or unchanged when plants were at 4 dpi. Then transcriptome sequencing for rust + or rust- Pnd leaves at 4 dpi was performed and interaction network of Pnd-ERFs and their target genes were predicted and analyzed. Based on the results of the transcriptome sequencing, transcript levels of 93 Pnd-ERF genes in rust + Pnd leaves were significantly different from those in rust- Pnd leaves, including 21 upregulated and 72 downregulated genes. In addition, 199 target genes were predicted to be regulated by 24 Pnd-ERFs in 216 interactions. Among them, only 31 target genes were activated, whereas 70 target genes were unchanged and the remaining 98 target genes were repressed. GO enrichment analysis indicated that most disease resistance-related target genes of Pnd-ERFs from rust + Pnd leaves were downregulated compared with their transcript levels in rust- Pnd leaves. Nevertheless, a negative regulator of plant innate immunity, the histone deacetylase 1 gene, which was targeted by a transcriptional repressor, Pnd-ERF40, was dramatically upregulated at 4 dpi. The inactivation of most Pnd-ERF genes and their disease resistance-related target genes, along with the activation of the negative regulator of plant innate immunity, at 4 dpi might account for the susceptibility of Pnd. Therefore, the inactivation of the Pnd-ERF gene network at the crucial time point should work on the breaking down of the resistance of Pnd. Highlights: There were 143 putative distinct ERFs identified from a E4-susceptible hybrid poplar,   Populus nigra×P. deltoides . Significant downregulations of ERF s mostly happened when E4 was at biotrophic period. The inactivation of most ERF genes and disease-related target genes and the activation of negative regulator in plant innate immunity might be related to the susceptibility of  P. nigra×P. deltoides  to E4.